Novel photodriven composite phase change materials with bioinspired modification of BN for solar-thermal energy conversion and storage. Issue 24 (6th June 2016) - Yang, Jie; Qi, Guo-Qiang; Tang, Li-Sheng; Bao, Rui-Ying; Bai, Lu; Liu, Zheng-Ying; Yang, Wei; Xie, Bang-Hu; Yang, Ming-Bo
Abstract : A novel design guidance for the preparation of photodriven composite PCMs with greatly enhanced thermal conductivity based on the bioinspired modification of BN for solar-thermal energy storage is provided. Abstract : The development of solar energy conversion and storage materials is critical to narrow the mismatch between the supply and demand of energy and to alleviate the environmental impact related to energy consumption in the coming years. Herein, novel photodriven composite phase change materials (PCMs) based on the bioinspired modification of boron nitride (BN) with superior solar-thermal energy conversion and storage performance are reported. The obtained composite PCMs show excellent performance in UV-vis sunlight harvesting, photothermal conversion, thermal energy storage, electrical insulation, shape-stabilization and high thermal conductivity. The preparation procedure is eco-friendly, easy to handle, and suitable for the practical application of energy materials based on polyethylene glycol (PEG)/polydopamine (PDA)@BN composites with enhanced performance for energy conversion and storage.